Mitoferrin-1 is Involved in the Progression of Alzheimer's Disease Through Targeting Mitochondrial Iron Metabolism in a Caenorhabditis elegans Model of Alzheimer's Disease. (10th August 2018) - Huang, Jiatao; Chen, Sixi; Hu, Li; Niu, Huan; Sun, Qianqian; Li, Wenna; Tan, Guoqian; Li, Jianghui; Jin, LongJin; Lyu, Jianxin; Zhou, Huaibin
Highlights: Down-regulation of MFN-1 increases lifespan in CL2006 and GMC101 nematodes. Down-regulation of MFN-1 reduces the paralysis rate and improves the progression of AD in Alzheimer model of C. elegans . Down-regulation of MFN-1 reduces mitochondrial iron content in Alzheimer model of C. elegans . Down-regulation of MFN-1 can affect mitochondrial iron metabolism and reduce mitochondrial ROS. Abstract: In mammals, mitoferrin-1 and mitoferrin-2, two homologous proteins of the mitochondrial solute carrier family are required for iron delivery into mitochondria. However, there is only one kind, called W02B12 ( mitoferrin-1 or mfn-1 ), in Caenorhabditis elegans and its regulatory mechanism is unknown. In this study, we used C. elegans strains CL2006 and GMC101 as models to investigate what role mitoferrin-1 played in Alzheimer's disease (AD). We found that knockdown of mitoferrin-1 by feeding-RNAi treatment extended lifespans of both strains of C. elegans . In addition, it reduced the paralysis rate in the GMC101 strain. These results suggest that mitoferrin-1 may be involved in the progression of Alzheimer's disease. Knockdown of mitoferrin-1 was seen to disturb mitochondrial morphology in the CB5600 strain. We tested whether knockdown of mitoferrin-1 could influence mitochondrial metabolism. Analysis of mitochondrial iron metabolism and mitochondrial ROS showed that knockdown of mitoferrin-1 could reduce mitochondrial iron content and reduce the level of mitochondrial ROS in the CL2006 and GMC101 strains. These results confirm that knockdown of mitoferrin-1 can slow the progress of disease in Alzheimer model of C. elegans and suggest that mitoferrin-1 plays a major role in mediating mitochondrial iron metabolism in this process.